The Relationship of Emoji-Based Self-Assessment, Teacher Role, and Student Perception with Learning Independence - Roasih, Roasih; Mulyono, Tri; Munadi, Munadi (LifeSciFi, 2026)
Learning independence is a crucial outcome in modern education, enabling students to take responsibility and initiative in their learning processes. This study examines the relationship between emoji-based self-assessment, teacher role, student perception, and learning independence among elementary school students. Using a quantitative correlational design, data were collected through questionnaires from 160 students familiar with digital learning activities. The instruments measured the four constructs using Likert scales, with reliability confirmed through acceptable Cronbach’s alpha values. The results show that emoji-based self-assessment, teacher role, and student perception are positively and significantly related to learning independence. Emoji-based assessment showed the strongest association, supporting students’ emotional awareness and self-reflection. Teacher guidance and supportive perception of the learning environment further contributed to autonomous learning behaviors. Collectively, these three factors explained 48% of the variance in learning independence. The findings imply that integrating simple, affective digital tools with supportive teaching practices can effectively foster student autonomy. Educators are encouraged to adopt emoji-based reflection methods, strengthen facilitative teacher roles, and cultivate positive classroom climates to promote independent learning, especially in technology-enhanced educational settings.